A new institutional perspective on shared spectrum access issues - Alison Bunel; Denis Lescop (International Telecommunications Society (ITS), 2013)
This paper analyzes the evolution of the Radio Spectrum Management (RSM) institution in Europe in the light of the New Institutional Economics. The paper uses the four levels of institutional analysis framework developed by Williamson to analyze and shed light on limits of the current RSM system. In this paper we focus particularly on the impact of technological change represented by the emergence of Cognitive Radio (CR) on level 2 and 3. The second level of institutional analysis refers to the formal rules of the games (institutional environment). We argue that the shift from exclusive and static to shared and dynamic use of spectrum is an institutional change fostered by the use of CR and the desire to meet spectrum-specific policy objectives. The third level of institutional analysis refers to the play of the game between actors with different objectives and strategies. Here, the reaction of incumbents and potential new entrants are discussed. It is shown that actors who want the change are trying to shape the rules of the game in order to get a competitive advantage whereas incumbents resist to the change. We conclude with main themes discussions and issues for future research.
Keywords: 330